Strategic Thinking in the EU – Aspiration or Reality? - Oana Mocanu; Mihai Sebe; Gabriela Andreica (Romanian Journal of European Affairs)
The aim of this paper is to show the most important points of view presented by high officials and representatives of the academic milieu from European countries on the occasion of the EPIN conference regarding the Strategic Thinking in the EU, held in Bucharest on September 30th, 2011. There were proposed to the audience several topics related to macro-regional strategies such as: Danube Strategy and Baltic Sea Strategy, the Europe 2020 Strategy and some key points on strategic thinking in EU foreign policy. The conference consisted of three sessions in which speakers stressed out the main topics of the day. The first session outlined the main aspects regarding the Baltic Sea Strategy and the Danube Strategy. The Europe 2020 Strategy was the central point of the second session of the conference, and in the last session, the speakers highlighted some important aspects on the strategic thinking in EU Foreign Policy. The series of speeches was completed by a Conclusions session in which the most important results of the debate were brought to the attention. Also, it left open for further discussion the need for the strategic thinking of the EU to become a reality.